Improved version of curd prepared by adding exopolysaccharides produced from a probiotic Lactobacillus paraplantarum KM1 - Sharma, Kanika; Sharma, Nivedita (Indian Journal of Dairy Science, 2019)
In the present study, sensorial, microbiological and physicochemical difference of three sets of curd were studied, as well as the changes taking place during storage at 4°C for 7 days. The 1st set of curd was produced with curd starter culture and exopolysaccharide (EPS) producing from lactic acid bacterial strain i.e. Lactobacillus paraplantarum KM1, the second set with curd starter culture with 0.2% (w/v) purified EPS i.e. producing from L. paraplantarum KM1 and the third with just curd starter culture (as control curd). Many changes were observed in terms of microbial evaluation; for all three set of curd, the viable count i.e. in log cfu/ml of curd increased till 3rd day i.e. for set A (13.05), set B (10.2) and set B (9.5) but after 3rd it showed a decrease in number, after 5th day significant difference occur between all three treatments during storage period at 4æ%C till 7 days. A decrease in pH followed by an increase in lactic acid was observed during storage for all three set of curd, which was mostly attributed to the activity of the curd starter culture. Curd made with purified EPS had significantly (P<0.05) lower firmness, low syneresis and higher viscosity values than control curd. According to the results, exopolysaccharide enhance viscosity, texture and mouth-feel and to avoid syneresis in curd. The results of this study suggest that the use of purified EPS could provide better textures for curd than those imparted by other chemical additives.